Combination of single-nucleus and bulk RNA-seq reveals the molecular mechanism of thalamus haemorrhage-induced central poststroke pain - Huang, Tianfeng; Xiao, Yinggang; Zhang, Yang; Ge, Yali; Gao, Ju (Frontiers in Immunology, 2023)
Central poststroke pain (CPSP) induced by thalamic haemorrhage (TH) can be continuous or intermittent and is accompanied by paresthesia, which seriously affects patient quality of life. Advanced insights into CPSP mechanisms and therapeutic strategies require a deeper understanding of the molecular processes of the thalamus. Here, using single-nucleus RNA sequencing (snRNA-seq), we sequenced the transcriptomes of 32332 brain cells, which revealed a total of four major cell types within the four thalamic samples from mice. Compared with the control group, the experimental group possessed the higher sensitivity to mechanical, thermal, and cold stimuli, and increased microglia numbers and decreased neuron numbers. We analysed a collection of differentially expressed genes and neuronal marker genes obtained from bulk RNA sequencing (bulk RNA-seq) data and found that Apoe, Abca1, and Hexb were key genes verified by immunofluorescence (IF). Immune infiltration analysis found that these key genes were closely related to macrophages, T cells, related chemokines, immune stimulators and receptors. Gene Ontology (GO) enrichment analysis also showed that the key genes were enriched in biological processes such as protein export from nucleus and protein sumoylation. In summary, using large-scale snRNA-seq, we have defined the transcriptional and cellular diversity in the brain after TH. Our identification of discrete cell types and differentially expressed genes within the thalamus can facilitate the development of new CPSP therapeutics.